Clinical Characteristics of Inpatients with Diabetic Foot Ulcer Admitted with Non-Ulcer Complaints: A Retrospective Study - Li L; Li Y; Qin S; Zeng J; Ma W; Wei D (Diabetes, Metabolic Syndrome and Obesity)
Lan Li,1,2 Yue Li,2,3 Shuang Qin,2 Jing Zeng,2 Wanxia Ma,2 Dong Wei2 1Medical Examination Center, Chengdu Second People’s Hospital, Chengdu, 610017, People’s Republic of China; 2Department of Endocrinology and Metabolism, Diabetic Foot Care Center, Chengdu Second People’s Hospital, Chengdu, 610017, People’s Republic of China; 3Department of Clinical Medicine, Chengdu Medical College, Chengdu, 610500, People’s Republic of ChinaCorrespondence: Dong Wei, Department of Endocrinology and Metabolism, Diabetic Foot Care Center, The Chengdu Second People’s Hospital, Chengdu, Sichuan, 610017, People’s Republic of China, Tel/Fax +86 02867830801, Email weidong314@126.comBackground: Diabetic foot ulcer (DFU) inpatients admitted with non-ulcer complaints constitute a neglected group that might suffer from more non-standard treatments. This study intends to describe their clinical characteristics, and clarify the problems existing in the DFU management process.Methods: In this retrospective study, admission complaints were determined by combining the final diagnosis and clinical documentation, and were categorized as: ulcer-related or non-ulcer complaints.Results: A total of 264 DFU inpatients were included in the final analysis, of which, 80 (30.3%) were admitted with non-ulcer complaints. A total of 82.5% of the DFU inpatients with non-ulcer complaints were admitted to departments without DF specialists. IWGDF/IDSA grade, cerebrovascular diseases, chronic kidney disease, infection in other parts, glycosylated hemoglobin A1c and the source of hospitalization expenses were the independent influencing factors for admission with non-ulcer complaints (all P < 0.05). Before admission, only 11.3% of the patients with non-ulcer complaints had ever been treated by a DF specialist and/or in a clinical setting with DF specialists. After admission, 25.0% of the DFU inpatients with non-ulcer complaints did not receive any local wound care, and only 7.6% of the patients admitted to the departments without DF specialists obtained a referral.Conclusion: Approximately one-third of inpatients with DFU are admitted with non-ulcer complaints and most of them are admitted to departments without DF specialists. Inpatients with non-ulcer complaints have milder wounds but more severe and greater comorbidities and worse organ function. These patients do not receive standardized management for DFU either before or after admission. Targeted measures are needed to improve this situation.Keywords: diabetic foot ulcer, admission complaint, non-ulcer, non-specialist